(untitled) (Damascus University Journal of agriculture sciences, 2023)
This research was aimed to replace wheat flour partially, with pomegranate peel powder at different proportions (0, 2, 4 and 6%), and study the effect of pomegranate peel powder on (color, moisture, ash, total phenolic content, antioxidant activity indices) and organoleptic properties of biscuits. Pomegranate peel powder sample showed a significant increase in the content of total sugars (25.86 g / 100 g dry weight), ash (3.93%), and a significant decrease in the percentage of moisture (7.52%) and proteins (0.70%). Also, these samples showed a significant increase in their total phenols content (206 mg / 100 g dry weight) and antioxidant activity (63.85%). Biscuit samples fortified with pomegranate peel powder with 6% showed a significant increase in total sugars (50.10 g / 100 g dry weight), ash (2.10%), total phenols content (136.65 mg/100g dry weight) and antioxidant activity (72.89%), compared with other biscuit samples. Also, this proportion improved taste, aroma, texture and general acceptability compared with control biscuit samples. Substitution proportion 2% of pomegranate peel powder had the greatest significant effect on reducing moisture content of biscuit samples, reached (6.34%) compared to of control biscuit sample (7.82%). High substitution proportion of pomegranate peel powder led to a significant increase in the content of total phenols by (134.83% to 191.99%) and a significant increase in antioxidant activity, at a rate ranging from (60.52% to 173.30%) compared with control samples.